Karakteristik Fisik, Kimia, dan Biologi Tempat Perindukan Potensial Nyamuk Anopheles sp. di Wilayah Kerja Puskesmas Hanura - Septilia Sugiarti; Riyan Wahyudo; Betta Kurniawan; Jhons Fatriyadi Suwandi (CV. Jasa Sukses Abadi, 2020)
Malaria is an infectious disease transmitted through mosquitoes and has become a health problem both in the world and Indonesia especially in Lampung. The population of the malaria vector is strongly influenced by the location of the breeding place. This study will examine the characteristics of breeding place of Anopheles sp as the malaria vector. This was an observational descriptive study conducted in the work area of Puskesmas Hanura Kabupaten Pesawaran. The physical characteristics has done by measuring temperature and water depth, the chemical characteristics by measuring pH and water salinity, and the biological characteristics by looking at organisms found at the sampling site. The breeding places are damaged boat, lagun, ditch, rice fields and abandoned ponds. The characteristics of the breeding palces are water temperature 29.5-32.4°C, water depth 10.1-28.6 cm, pH 5-6.6, salinity 0-9.3. Predators found in the breeding place are Aplocheilus panchax (tin head fish), Gambusia affinis (Cere Fish), Culex sp. (larvae stages), Aedes sp. (larvae stages), and water plants Ocsillatoria sp. (alga), Spirogyra (alga). Physical, chemical, and biological characteristics of Anopheles sp. breeding place in Puskesmas Hanura working area are optimum characteristics for Anopheles sp. breeding.